2022
DOI: 10.3389/fragi.2022.1058435
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-induced cardiotoxicity and senescence

Abstract: Cancer continues to place a heavy burden on healthcare systems around the world. Although cancer survivorship continues to improve, cardiotoxicity leading to cardiomyopathy and heart failure as a consequence of cancer therapy is rising, and yesterday’s cancer survivors are fast becoming today’s heart failure patients. Although the mechanisms driving cardiotoxicity are complex, cellular senescence is gaining attention as a major contributor to chemotherapy-induced cardiotoxicity and, therefore, may also represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Moreover, while cellular senescence is a well-recognized response to chemotherapy drugs, it has attracted attention for its connection to chemotherapy-induced cardiotoxicity. Consistently, the removal of senescent cells has been correlated with a reduction in the pathophysiology of cardiovascular disease and with the prevention of myocardial dysfunction in relation to chemotherapy-induced cardiotoxicity [ 15 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, previous studies have reported DOX’s ability to induce cellular senescence in fibroblast cells, including CFs [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, while cellular senescence is a well-recognized response to chemotherapy drugs, it has attracted attention for its connection to chemotherapy-induced cardiotoxicity. Consistently, the removal of senescent cells has been correlated with a reduction in the pathophysiology of cardiovascular disease and with the prevention of myocardial dysfunction in relation to chemotherapy-induced cardiotoxicity [ 15 , 50 , 51 , 52 , 53 , 54 ]. Furthermore, previous studies have reported DOX’s ability to induce cellular senescence in fibroblast cells, including CFs [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cellular senescence can be viewed as an example of antagonistic pleiotropy, which is a cellular program which is beneficial in one setting but deleterious in another [15]. Within the cardiovascular system, models of induced and attenuated senescence have implicated senescence in the pathophysiology of myocardial remodelling (age-related, chemotherapy-induced [16], and post-injury) [3,4,[17][18][19], hypertension, atherosclerosis [20], and the development of aortic aneurysms [21], and have been extensively reviewed [22][23][24][25][26][27].…”
Section: Cellular Senescencementioning
confidence: 99%
“…Analysis of LV human heart tissue from patients with doxorubicin-induced cardiotoxicity has revealed increased expression of a range of markers of senescence in cardiomyocytes compared to LV tissue from healthy donors ( 125 ). In addition to cardiomyocytes, doxorubicin-induced senescence can potentially occur in cardiac fibroblasts and cardiac endothelial cells ( 126 ).…”
Section: Cardiotoxicitymentioning
confidence: 99%